PENGARUH MODAL TERHADAP SISA HASIL USAHA (Studi Kasus: KUD Lalung Jaya Karanganyar tahun 2008-2009) - ., Sarsiti (Universitas Surakarta, 2012)
This study is a descriptive study, to obtain a picture of the influence of capital to the rest of the results of operations. The population used in this study are the financial statements of KUD Lalung Jaya Karanganyar 2008-2009. Data collection techniques used method of documentation, interviews, and observations. The data obtained and the analysis of test requirements. Technical analysis of the data used is multiple regression analysis, the F-test, t-test, and determination (R2). The results of the regression analysis to get the value of F>F or 195,532>19,0 (significance level of 5 %). Means between capital variable X is jointly affect business revenue (Y). Results obtained regression equation Y = -3284976320 + 0,258 X. The calculations show that t for capital X at 2,703<4,30, which means capital X significantly influence of net income (Y) (5% significance level). The coefficient of determination (R) 2 by 0,895 so that it can be said that the results of tests performed cuku give good results. The coefficient of determination is positive, it indicates that 89,5 % of the variation of net income can be explained by the variable capital while the remaining 10,5 % can be explained by other variables outside the model of this study. Keywords; Capital, and the rest of the results of operations.